Histomorphology of gastrointestinal tract in bullfrog Rana (Lithobates) catesbeiana and evaluation of the changes induced by a soybean meal‐based diet. (9th October 2019) - Yang, Manqi; Rahimnejad, Samad; Zhang, Chunxiao; Song, Kai; Lu, Kangle; Wang, Ling
Abstract: Two studies were carried out to (a) characterize the gastrointestinal (GI) tract of bullfrog Rana ( Lithobates ) catesbeiana and (b) to evaluate the effects of total replacement of fish meal (FM) with soybean meal (SBM) on GI tract health. For characterization of the GI tract, oesophagus, stomach and intestine sections were sampled from 20 bullfrogs (80 g) fed a FM‐based diet. The results revealed that the GI tract of bullfrog is consisted of four tissue layers including mucosa, submucosa, muscularis and serosa, and that the intestine could be divided into duodenum, jejunum, ileum and rectum. Furthermore, the abundance and length of mucosal folds suggested that jejunum is the primary site of digestion and absorption of nutrients. In the second study, a diet containing 44% fish meal (FM) was formulated and used as a FM‐based diet, and a SBM‐based diet was prepared by entire substitution of FM with SBM. Sixty bullfrogs (35 ± 1 g) were divided into three replicates of the two groups and were fed the test diets to apparent satiation twice daily for 8 weeks. The changes in pH and morphology of GI tract in response to the shift in dietary protein source were evaluated. The results showed the enhancement of pH values in GI tract of the SBM group excluding cardia, jejunum and rectum. Also, SBM diet triggered significant decreases in the number, height and width of mucosal folds, while an opposite trend was observed for thickness of lamina propria. Moreover, the entire replacement of FM with SBM led to the separation of submucosa from muscularis and incidence of lesion in mucous epithelium. The findings in this study showed that jejunum is the main site of nutrients digestion and absorption. Also, it was demonstrated that entire replacement of FM with SBM adversely influenced the GI tract health in bullfrog.